Analisis Nilai KeIslaman tentang Hadits Tasyabbuh dalam Perspektif Gen Z - Tamimatun Nihayah; Nasrulloh (Al-Kindi, 2026)
The rise of Korean popular culture (K-Pop) has become a significant part of the digital lives of Muslim Generation Z in Indonesia, functioning not only as entertainment but also as a medium for self-expression and cultural identity formation. However, this engagement with global culture raises questions regarding Islamic value boundaries, particularly in relation to the hadith on tasyabbuh, which cautions against imitating specific groups. This study aims to analyze how Muslim Gen Z understands the relevance of the tasyabbuh hadith and how they negotiate religious values with their identity as K-Pop fans. Using a quantitative survey design, data were collected through an online questionnaire distributed via purposive and snowball sampling to 35 Muslim respondents aged 17–25. Descriptive statistics were employed to map patterns of cultural consumption, hadith comprehension, and religious attitudes. The findings reveal that K-Pop consumption among Muslim Gen Z is selective, with most respondents viewing it as a neutral form of entertainment that does not interfere with religious practices. Their interpretation of the tasyabbuh hadith tends to be contextual, distinguishing between imitation in ritual matters and imitation in general cultural practices, leading them to conclude that engaging with K-Pop does not constitute prohibited imitation. Furthermore, respondents demonstrate strong moral filtering mechanisms and uphold religion as a primary boundary in interacting with popular culture. Thus, the study concludes that Muslim Gen Z’s engagement with K-Pop represents a moderate identity negotiation that remains rooted in Islamic values.